Prenatal DEHP exposure induces hippocampal neurotoxicity in male offspring via PTEN dysregulation and impaired Akt/mTOR and NMDA signaling: Possible mechanism of phthalates’ neurotoxicity - Kiknadze, Natalia; Zhuravliova, Elene; Mikeladze, David (Cellular and Molecular Biology, 2025)
Widespread human exposure to phthalates is caused by their intensive usage in industrial and consumer plastic products. DEHP (di(2-ethylhexyl) phthalate) is one of the most often used phthalates and is presented not only in food and fluids but also in the air and dust contact with plastic products. Regrettably, phthalates easily migrate into the human body and act as potent toxicants, mainly on endocrine and metabolic status. In the last decade, several epidemiological studies have indicated a correlation between prenatal exposure to phthalates and adverse effects on neurodevelopment in offspring. Our research aimed to assess the impact of DEHP prenatal subchronic exposure on male offspring's behavior and learning ability and identify the primary target brain structure/s of neurotoxic action. Heightened anxiety in male offspring was evident through increased rearing, frequent line crossings, hurried movements, and reduced grooming behavior. These behaviors were accompanied by a decline in recognition memory and diminished interest in exploring novel objects. Obtained data showed that prenatal oral exposure to DEHP in a selected concentration induces irreversible changes in brain structures of the male offspring, primarily in the hippocampus, that underlies significant alterations in cognitive behavior and enhanced anxiety. The molecular mechanism of DEHP-induced hippocampal neurotoxicity in the maturing male brain involves changes in phosphatase and tensin homolog (PTEN) subcellular location, which suppresses Akt/mTOR signaling, enhances GluN2B NMDA mediated synapse depression and decreases mitochondrial fusion.